2015
DOI: 10.1007/s10562-015-1555-y
|View full text |Cite
|
Sign up to set email alerts
|

CuII(Sal-Ala)/CuAlLDH Hybrid as Novel Efficient Catalyst for Artificial Superoxide Dismutase (SOD) and Cyclohexene Oxidation by H2O2

Abstract: This work presents Cu II (Sal-Ala) complex immobilized on the CuAlLDH as a novel efficient catalyst for artificial superoxide dismutase (SOD) enzyme activity and cyclohexene oxidation. The physico-chemical properties of Cu II (SalAla)/CuAlLDH were investigated by XRD, XPS, FTIR, DRUV and TGA techniques. The correlation between the catalytic performances, structure and composition of the hybrid catalyst is also discussed. Graphical Abstract& Mihaela Mureşeanu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…[7] However,s upplementation of SOD is difficult owing to its high sensitivity to environmentalc onditions (e.g.,t emperature, pH, and complex nature in biofluids). Therefore, significante fforts have been made to prepare metal complexes, [8][9][10][11][12] nanoparticles or colloidalp articles, [13] or their combinations [14][15][16][17][18] to obtain artificial SOD materials of similara ctivity,b ut with improved sensitivity relative to that of the native enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…[7] However,s upplementation of SOD is difficult owing to its high sensitivity to environmentalc onditions (e.g.,t emperature, pH, and complex nature in biofluids). Therefore, significante fforts have been made to prepare metal complexes, [8][9][10][11][12] nanoparticles or colloidalp articles, [13] or their combinations [14][15][16][17][18] to obtain artificial SOD materials of similara ctivity,b ut with improved sensitivity relative to that of the native enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of cyclohexene with H 2 O 2 in acetonitrile, under an air atmosphere, was selected as a test reaction to determine the catalytic performances of the SBA-15-supported Cu(II)-Schiff base complex. The optimization of the CH oxidation was previously performed [8] and the best operation parameters were established to be a 5 h reaction run at 60 • C with 0.03 mmol catalyst, 10 mL of solvent and a 2.2/1 H 2 O 2 /C 6 H 10 molar ratio. Synergic effects for the catalytic activity given by the SBA-15 silica surface and the acetonitrile solvent were observed.…”
Section: Catalytic Tests 221 Catalytic Performances Of the Cu(ii) Com...mentioning
confidence: 99%
“…Both CH conversion and TOF values were, however, slightly diminished after repeated use, probably due to a change in the morphology of the mesoporous material or in the catalytically active center surroundings. The biomimetic comportment of free or immobilized Cu(II)-BrAld complexes was tested for SOD activity [8]. All materials, except the silica support, presented catalytic activity in the dismutation reaction of superoxide radicals (O 2 − ).…”
Section: Stability Of Cu(ii) Complex/sba-15 In the Cyclohexene Oxidat...mentioning
confidence: 99%
See 1 more Smart Citation
“…For P1-Cu-3/1, Figure 3C revealed that both the binding energy and intensity in the N 1S region were greater than those of P1. Furthermore, there was a shoulder peak at 934.0 eV for Cu 2p 3/2 peaks (Figure 3D), which could be attributed to the Cu/N coordination complex, and the shake-up peaks at 939.9-943.9 eV and at 962.8 eV indicated the presence of partly coordinated Cu 2+ [29,30]. The charging of the electron cloud environments of the N and Cu atoms indicated that the lone pair electrons of the nitrogen atoms transferred to the empty orbitals of Cu 2+ ions, contributing to the physical crosslinking of the obtained elastomers.…”
Section: Hydrogen-bonded and Metal-coordinated Elastomersmentioning
confidence: 99%